Upaya Kebijakan Kriminalisasi dalam Penegakan Hukum Tindakan Prank di Masyarakat Melalui Saluran Streaming - Tian Terina; Muhamad Rusjana; Dery Hendryan (Universitas Sang Bumi Ruwa Jurai, 2023)
The aim of the prank is to make the person, in this case the victim, feel pranked, thereby creating a sense of satisfaction in the prank maker. There are various types of pranks, including pranks that use a crime theme, such as kidnapping, pointing a sharp weapon, or acting as a thug who pretends to threaten the victim of his prank. However, not all pranks end in jokes or antics, excessive pranking can cause losses and also victims. These prank actions include actions that create pros and cons, whether these actions can fall into the category of criminal acts that require criminal sanctions or are just guidance.